Familial Melanoma Phenotype With Xeroderma Pigmentosum Group C (XP-C) Genotype - The Putative Role of MC1R Polymorphism as Modifier - Franciele Antonieta Bianchi Leidenz; Flavia Vasques Bittencourt; Williana Garcia Braga; Ellio Magno de Sá Araujo; Carolina Cavalieri Gomes; Vanessa de Fatima Bernardes; Eitan Friedman; Luiz De Marco (Dermatology Practical & Conceptual, 2024)
Introduction: Xeroderma pigmentosum (XP), a rare inherited condition, hallmarked by extreme sensitivity to sun exposure resulting in multiple skin cancers and non-malignant skin alterations is attributed to homozygous inactivating pathogenic variants (PVs) in DNA repair genes, predominantly the XPC gene.